(untitled) (Global Journal of Management and Business Research, 2013)
We make a comparative study of Multifractal Detrended Fluctuation Analysis (MF DFA) and the Wavelet Transform Modulus Maxima (WTMM) method to detect multifractal character of natural gas daily returns. We give a brief introduction on above methods and compare their effectiveness. The results from this methodoligies show that behaviour of natural gas daily returns were multifractal. The major sources of multifractality are long-range correlations of small and large fluctuations and Fat-tail distributions of the series.